Les formes alternatives de défense : l’exemple européen - Galtung, Johan (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The time has come to discuss military doctrine. We have, for much too long now, been discussing separate weapon Systems, sometimes singly, sometimes combined, and not the underlying rational. This article spells out alternative security policies in the fields of military and foreign policies. The reader will find a layman's guide to military doctrine, beginning with a basic distinction made between offensive and defensive postures, a distinction based on capability and not on intention. We will show that the division into military and political motivations is far from sharp, and needs to be better understood in order to discuss and assess the implications of alternative doctrines for Europe.